Differential gut microbiome composition in three-spined stickleback populations with contrasting levels of mercury accumulation - Kuizenga, Marijn; Shankregowda, Aruna M.; Siriyappagouder, Prabhugouda; Delahaut, Vyshal; Calboli, Federico C. F.; Bervoets, Lieven; Yadav, Brijesh Singh; Volckaert, Filip A. M.; De Boeck, Gudrun; Raeymaekers, Joost A. M. (Frontiers in Microbiology, 2026)
IntroductionEnvironmental micropollutants and other anthropogenic xenobiotics are potential drivers behind compositional shifts and functional dysregulation of gut microbial communities. Mercury and many of its compounds are highly toxic and ubiquitous environmental pollutants that pose a risk for aquatic biota and humans. Here we compared the gut microbial communities of natural three-spined stickleback (Gasterosteus aculeatus Linnaeus, 1758) populations in Flanders, Belgium, with contrasting muscle mercury concentrations. We hypothesized that exposure to a high mercury load selects for gut flora species with the capacity to tolerate or adapt to this stressor and, thus, leads to a change in the composition of the gut microbiota.MethodsThe gut microbiota of 128 host individuals from four populations with low levels of accumulated mercury and four populations with high mercury levels were characterized using 16S rRNA amplicon sequencing. Gut microbial communities were compared across host muscle mercury content levels, host populations and sexes to consider the contribution of these factors in the observed differences in gut microbial diversity and composition.ResultsMicrobial community composition varied significantly between males and females, as well as between host populations with high and low muscle mercury content. While the abundance of 22 amplicon sequence variants (ASVs) was associated with the host’s muscle mercury content, we detected no specific indicator species for high mercury.ConclusionOverall, our results suggest that local factors specific to a host population, potentially including mercury accumulation and sex-specific factors, differentiate the microbial communities inhabiting the gastrointestinal tracts of the three-spined stickleback.